PENGARUH LOYALITAS KARYAWAN, TUNJANGAN KARYAWAN DAN KOMUNIKASI KERJA TERHADAP KINERJA KARYAWAN UD BUDI JAYA ABADI - Nuryani, Ni Nyoman Juli; Yanti, Komang Fryday (Jurnal Daya Saing, 2023)
The phenomenon at the beginning of the researchers found a lack of awareness of UD Budi JayaAbadi employees. Employee performance requires awareness from employees to develop the company. Thisstudy aims to examine the effect of employee loyalty, employee benefits and work communication onemployee performance at UD Budi Jaya Abadi employees. The type of data used in this research isquantitative data and qualitative data. The population in this study were 35 employees of UD Budi JayaAbadi. The number of samples in this study were all employees of UD Budi Jaya Abadi, namely as many as35 people and used a saturated sampling technique. The findings in this study are (1) There is an influenceof employee loyalty on employee performance. Employee loyalty is able to improve employee performanceto achieve higher performance. (2) There is an influence of employee benefits on employee performance.Allowances or fair compensation can be a motivating factor for employees to improve employeeperformance. (3) There is an influence of work communication on employee performance. Workcommunication can increase the efficiency and effectiveness of employees in achieving the desiredperformance.